Methicillin-Resistant Staphylococcus aureus (MRSA) Detection from the Hands of Jatinangor Community Health Centerâs Health Care Providers - Patmanathan, Jeevanisha; Sudigdoadi, Sunarjati; Adriansjah, Ricky (Althea Medical Journal, 2015)
Background: Methicillin-resistant Staphylococcus aureus is a bacterium that is resistance towards Î²-lactamÂ antibiotics, and it seems to be one of the leading causes of nosocomial infections. Hands of the health careÂ workers are said to be the main source for the nosocomial transmission. Thus, the study aims to determineÂ methicillin-resistant S. aureus from the hands of Jatinangor Community Health Centerâs health care workers.Methods: Samples were taken from the hands of 30 Jatinangor Community Health Centerâs staffs, includingÂ medical and paramedical; from October 2012 to November 2012. Then, these samples underwent furtherÂ laboratory examinations, starting from culture, identification and susceptibility test towards cefoxitin, inÂ identifying methicillin-resistant S. aureus.Results: Out of the 30 samples taken, 6 samples (20%) were positive for S. aureus isolates. In which, 4Â (13.33%) of the samples were positive for methicillin-resistant S. aureus.Conclusions: Since, health care workers are the main people in contact with patients and maintainingÂ proper hand hygiene makes a huge difference; hand hygiene should be given adequate attention for theÂ benefit of all. [AMJ.2015;2(1):217â20]